Shape-selective, stoichiometric sensing of fatty acids with a mixed polydiacetylene liposome. Issue 14 (20th October 2015) - Cho, Yong-Suk; Ma, Dong Hee; Ahn, Kyo Han
Abstract : A mixed polymerized liposome discriminates fatty acids depending on their overall shape and with a discrete binding stoichiometry. Abstract : Unsaturated fatty acids exert diverse biological processes dependent on their overall shape due to cis and trans isomerism. Hence selective detection of fatty acids by their molecular shape is of interest but is a challenging goal. Disclosed here is a polymerized liposome that selectively senses bent fatty acids over linear fatty acids, with a turn-on type fluorescence change as well as a distinct color change from blue to red. The use of two different liposome components that contain monoamine and triamine moieties is found to be critical for the color change. Furthermore, the color change can be correlated with a distinct stoichiometry between the molar ratio of the total liposome components and an analyte cis -fatty acid, oleic acid, in a ratio of 1 : 2. The colorimetric response also shows good linearity up to the equivalent point, which enables the monitoring of the content change of cis -fatty acids in commercial cooking oil upon heating at 200 °C.